2020
DOI: 10.3390/su12062368
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Determinants of Strategic Corporate Social Responsibility: An Empirical Examination

Abstract: A growing number of studies propose that the performance outcomes of Corporate Social Responsibility (CSR hereafter) are dependent upon how firms implement CSR. If firms are able to strategically implement CSR, their CSR engagement will not only improve stockholders' value, but will also contribute to corporate sustainability. However, research on strategic CSR is still incipient. This study aims to examine the determinants of strategic CSR. Taking firms that have published CSR reports for three consecutive ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 91 publications
0
24
0
Order By: Relevance
“…Past research conducted by Ozcan (2019), stated that leverage has a positive and significant impact on SR disclosure, which means that firms have greater resource availability and lead to a higher number of activities to disclose. In line with this statement, Yu & Liang's (2020) research also found that leverage has a significant positive impact on SR disclosure, while Fahad & Nidheesh (2020) stated that leverage has a positive impact on environmental and social disclosure on SR and has a negative impact on SR disclosure. Disclosure of governance in SR. Another case with research done by Akbulut & Kaya (2019) and Abdulsalam & Babangida (2020) stated that leverage with SR disclosure has a significant [39] negative impact because firms with a higher level of dependence on debt will prevent firms from investing in a sustainable manner.…”
Section: H1 : Firm Size Has a Positive Impact On Sr Disclosurementioning
confidence: 60%
See 2 more Smart Citations
“…Past research conducted by Ozcan (2019), stated that leverage has a positive and significant impact on SR disclosure, which means that firms have greater resource availability and lead to a higher number of activities to disclose. In line with this statement, Yu & Liang's (2020) research also found that leverage has a significant positive impact on SR disclosure, while Fahad & Nidheesh (2020) stated that leverage has a positive impact on environmental and social disclosure on SR and has a negative impact on SR disclosure. Disclosure of governance in SR. Another case with research done by Akbulut & Kaya (2019) and Abdulsalam & Babangida (2020) stated that leverage with SR disclosure has a significant [39] negative impact because firms with a higher level of dependence on debt will prevent firms from investing in a sustainable manner.…”
Section: H1 : Firm Size Has a Positive Impact On Sr Disclosurementioning
confidence: 60%
“…Media visibility is a medium for transparency of firm information with its aim of being recognized by the public (Humanitisri & Ghozali, 2018) and communicating with investors (OuYang et al, 2017). When a firm has a great and big reputation, the firm experiences greater pressure in maintaining its strong reputation, like fulfilling the demands of stakeholders by expressing and engaging in their social responsibility activities (Yu & Liang, 2020). One of the past studies stated that media visibility is an external determinant which is consistently found to have a significant positive impact on SR disclosure (Dienes et al, 2016).…”
Section: H3: Firm Age Has a Positive Impact On Sr Disclosurementioning
confidence: 99%
See 1 more Smart Citation
“…Second, strategic CSR stresses the coexistence of business and social benefits [26,27,31]. Since strategic CSR incorporates social objectives into business and links social and economic goals in the long term [32], firms need to perform a benefit analysis before making a decision to carry out a CSR initiative [33]. The motivation of strategic CSR is to benefit society and the firm simultaneously, improving the social and firm value and achieving a win-win situation [27,32].…”
Section: Strategic Corporate Social Responsibilitymentioning
confidence: 99%
“…In their study, Yu and Liang [18] examined the role of corporate social responsibility in the strategic planning process. In this study, it was stated that in addition to reducing costs, integrating organizational resources and using the creativity and decision-making power of all employees at all levels, social responsibility was also perceived as strategic capability.…”
Section: Research Backgroundmentioning
confidence: 99%